(untitled) (Journal of the College of Basic Education, 2023)
The twentieth century saw a very great development of structuralism and linguistics after the publication of Saussure’s lectures, which took a great deal of translation into several languages in the world. By studying its analyzes, contextual references, and its external factors affecting its communication processes between the conductor and the recipient, which led to the emergence of multiple and new currents and theories that scholars called the term pragmatic and they refer to the function of language and the extent to which our daily lives are affected in terms of their levels of differences. The first chapter (the methodological framework), which includes The research problem represented in the following question: How can pragmatic be achieved in theatrical performance and with the aim of achieving the chromatic values of this? The importance of research and the need for it lies with those who need it from specialists and researchers. The aim of the research is to find correct scientific bases that can reach the deliberative results in the influence of color values. The limits of the research consisting of time, place and topic represented in a directing presentation in the theater of the capital, Baghdad by the professors of the College of Fine Arts at the University of Baghdad for the limited period (2016) pragmatic in the ritual theatrical performance. Defining the terms and their definitions that fit with what the research aims at.The second chapter (theoretical framework) was devoted by the researcher to the study of the following (Chapter One) Deliberative and its emergence (The second topic) the foundations of color values in terms of the type of color, its connotations, and its functions in the performances of the ritual theater. Reaching to the indicators reached by the researcher from the theoretical framework that adopted the criteria of analysis for the sample of the research. Previous studies and their approach to research content As for the third chapter, which includes the research procedures identified by the research community that the researcher followed with (the descriptive approach) and the use of the theanalysis method in which I analyzed the research sample that was presented by the professors of the Faculty of Fine Arts, Department of Dramatic Arts, Al-Rowad Theater, a play (Greeb Al Dar) written and directed by (Dr. Zuhair Kazem)The fourth chapter resulted from the theoretical framework of indicators adopted by the researcher in analyzing the proven research sample with the resultsThen the conclusions that were extracted from the research results with recommendations and suggestions, a list of sources and a summary of the research in English